The Effect of Perceived Organizational Support on Employee Performance - Weny Weny; Rina Friska Br Siahaan; Dewi Anggraini; Fahmi Sulaiman (Institute of Computer Science (IOCS), 2021)
Employee performance is relevant to researched, because nowadays many performances are not paid attention to even though a good performance can have a big influence on every company, as well as to find out whether employees work responsibly or not. Good performance will produce satisfactory quality and quantity, but on the other hand, poor performance will produce poor results. This is a special concern within the company, in achieving the company's goals effectively and efficiently through good performance. Every organization always wants satisfactory performance in achieving the goals of the company. There are several factors that affect employee performance, which are Perceived Organizational Support (POS). The problem is the decreasing of employee performance in Medan Cendana Polytechnic due to the decrease in Perceived Organizational Support. This will affect in a decrease of employee engagement. The research objective is an effort to improve employee performance in terms of Perceived Organizational Support and employee engagement. There are several steps in this research, which are distributing questionnaires, recapitulating the results of the questionnaires and analyzing the results with statistics. The results of the research show that based on the partial test data processing (T test) the significance value is below 0.05, which means that there is a relationship between Perceived Organizational Support and Cendana Polytechnic employee performance. The results also show that the employee engagement variable mediates the relationship between Perceived Organizational Support on performance because after the three mediation test conditions are met, the researcher compares the effect of Perceived Organizational Support on employee performance in model 2 and 3. As a result, the effect of Perceived Organizational Support on employee performance in model 3 is weak, this means that there is a partial mediation effect.